Rodent Models of Developmental Ischemic Stroke for Translational Research: Strengths and Weaknesses - Mariangela Gennaro; Alessandro Mattiello; Tommaso Pizzorusso (Neural Plasticity)
Cerebral ischemia can occur at any stage in life, but clinical consequences greatly differ depending on the developmental stage of the affected brain structures. Timing of the lesion occurrence seems to be critical, as it strongly interferes with neuronal circuit development and determines the way spontaneous plasticity takes place. Translational stroke research requires the use of animal models as they represent a reliable tool to understand the pathogenic mechanisms underlying the generation, progression, and pathological consequences of a stroke. Moreover, in vivo experiments are instrumental to investigate new therapeutic strategies and the best temporal window of intervention. Differently from adults, very few models of the human developmental stroke have been characterized, and most of them have been established in rodents. The models currently used provide a better understanding of the molecular factors involved in the effects of ischemia; however, they still hold many limitations due to matching developmental stages across different species and the complexity of the human disorder that hardly can be described by segregated variables. In this review, we summarize the key factors contributing to neonatal brain vulnerability to ischemic strokes and we provide an overview of the advantages and limitations of the currently available models to recapitulate different aspects of the human developmental stroke.